Hubungan antara Self-Confidence dan Self-Acceptance Terhadap Konstruksi Meaning of Life Siswa Digital Native - Fhyna Anggraeni Yuniantika; Nur Hidayah (JKI (Jurnal Konseling Indonesia), 2026)
This study aims to examine the correlation of Self-Confidence and Self-Acceptance in the Construction of Meaning of Life of Digital Native Students. This study uses a quantitative approach with a correlational design. A total of 203 students of SMAN 1 Kepanjen as respondents were determined through a simple random sampling technique. The data collection instruments consisted of questionnaires, all three of which have been tested for validity with a load factor value of > 0.50. The results showed that the three variables were in the high category, namely self-confidence at 74%, self-acceptance at 49%, and 49% at the level of meaning of life. There was a simultaneous positive and significant relationship to the meaning of life at 0.680. The results of the linear regression analysis showed that simultaneously 37% of the meaning of life was influenced by self-confidence and self-acceptance. This finding confirms the importance of strengthening students' self-confidence, self-acceptance, and meaning of life optimally. Suggestions for further research are to 1) develop further, more in-depth studies of self-confidence, self-acceptance, and meaning of life with other influential variables, 2) design appropriate interventions to improve students' meaning of life.